Pemberdayaan Masyarakat Melalui Pengembangan Potensi Perkebunan Dan Hortikultura Lereng Di Kecamatan Ciawi, Kabupaten Tasikmalaya - R. Hozin Abdul Fatah; Siti Amirah Makarim; Akhmad Hidayat Nurul Akbar (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2026)
This community service program aims to empower the people of Ciawi District, Tasikmalaya Regency, by developing plantation and horticultural potential on sloping land. This region boasts agro-ecological conditions that support the development of various superior commodities, such as chilies, coffee, and palm sugar. However, exploiting this potential still faces several obstacles, including vulnerability to erosion and land degradation, limited application of cultivation and post-harvest technologies, and suboptimal marketing access. The methods used in this community service activity included identifying superior commodities, a SWOT analysis to develop development strategies, and implementing cultivation and post-harvest technologies appropriate to the characteristics of sloping land. Furthermore, the activity was carried out using a participatory approach through training and mentoring for farmers. The results of the activity indicate that Ciawi District has significant potential for developing chilies, coffee, and palm sugar commodities, but requires sustainable land management and more innovative marketing strategies. The community empowerment strategies implemented include terracing as a land conservation measure, diversification of processed products to increase added value, and the use of digital marketing. This approach has been proven to increase agricultural productivity, product diversification, and strengthening community institutions, thus contributing to improving the economic welfare of the community in a sustainable manner.